Brazilian isolates of Trypanosoma cruzi from humans and triatomines classified into two lineages using mini-exon and ribosomal RNA sequences - Fernandes, Octávio (American Journal of Tropical Medicine and Hygiene, 2020)
Traditional molecular and biochemical methods, such as schizodeme analysis, karyotyping, DNA fingerprinting, and enzyme electrophoretic profiles, have shown a large variability among Trypanosoma cruzi isolates. In contrast to those results, polymerase chain reaction (PCR) amplification of sequences from the 24Sα ribosomal RNA gene and from the mini-exon gene nontranscribed spacer indicated a dimorphism among T. cruzi isolates, which enabled the definition of two major parasite lineages. In the present study, 86 T. cruzi field stocks (68 isolated from humans with defined presentations of Chagas' disease and 18 from triatomines) derived from four Brazilian geographic areas were typed by the PCR assay based on the DNA sequences of the mini-exon and 24Sα rRNA genes. These stocks were ordered into the two major T. cruzi lineages. Lineage I was associated mainly with human isolates and lineage 2 with the sylvatic cycle of the parasite.